If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 20 + n Solving 25 = 20 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 25 + -1n = 20 + n + -1n Combine like terms: n + -1n = 0 25 + -1n = 20 + 0 25 + -1n = 20 Add '-25' to each side of the equation. 25 + -25 + -1n = 20 + -25 Combine like terms: 25 + -25 = 0 0 + -1n = 20 + -25 -1n = 20 + -25 Combine like terms: 20 + -25 = -5 -1n = -5 Divide each side by '-1'. n = 5 Simplifying n = 5
| 7(8)+4(-8)= | | .25y+3=-8 | | 14+z=29 | | q^2-5q-36=0 | | 7(8.4)+4(-8.3)=24 | | 5x+6(-8.3)=-8 | | 0.60x+0.05(12-x)=0.10(-38) | | p^2+8p-48=0 | | 5(3.4+-0.6y)+6y=-8 | | 5x^4-38x^2-16=0 | | g^2-11g+30=0 | | 17.25=x+(x*.15) | | 10x-4=0 | | 52=4x-16 | | -9(-1)+4(-3.1)= | | 3(-1)-7(-3.1)= | | 6xy=10+-4y | | -x/3=-2 | | 9(t-5)+6t=5(3t+3)-10 | | 27X-90+40X+60+20=3X+18+16+68X | | -9x+4(-3.1)=-3 | | 5f/3=-7 | | 4+4s-2=9s+4-3s | | -9(6+2.3y)+4y=-3 | | 7.5x=2000 | | 2(3x-1)-(4x-3)+x=5(x+2)-3(x-2)-15 | | 3(6)-7(0)= | | 5x-1+2=10 | | (5/8)^-1 | | 3x-7(0)=18 | | 3(6+2.3y)-7y=18 | | 37X-90+40=12X+25X+50 |